Investigation of Hybrid Solvents for Absorption of CO2 - Lai, Chun Hoe (Universiti Teknologi PETRONAS, 2016)
The main purpose of this project work is to investigate hybrid solvents of ionic liquidsamines mixture for CO2 absorption. Tertiary amine methyldiethanolamine (MDEA) is being widely used in the industries as one of CO2 capturing technologies. However these amine solvents have limitations and there are many emerging technologies under development. Ionic liquid (IL) is a new emerging solvent which is regarded as potential alternative due to its tuneable and physicochemical properties, also possess some drawbacks including its high viscosity and low CO2 loading capacity. New research works are being conducted in developing novel hybrid solvents i.e. mixture of ionic liquids and amines with enhanced performance in terms of CO2 absorption by bringing out the strengths of each solvent while suppressing their limitations.